Characteristic Nutritional Composition, Protein Digestibility, and Total Lactic Acid Bacteria of Plant-Based Yogurt from Different Legume - Anisa Rachma Sari; Mita Nurul Azkia; Ika Fitriana; Zulhaq Dahri Siqhny; Farezha Ilham Raihanda Putra; Amanda Ridho Sugiharto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2026)
Several types of local Indonesian legume have the potential to be developed into plant-based milk yogurt, including pigeon peas, soybeans, and mungbeans. However, the protein contained in legume milk is characterized by low digestibility and bioavailability, underscoring the need to combine several types of legume and proper bioprocessing. Fermentation of legume milk by L. bulgaricus and S. thermophilus has been shown to improve the sensory and nutritional value of yogurt. Therefore, this study aims to analyze the nutritional value, protein digestibility, and total LAB of yogurt from a single type of legume (pigeon peas) and a combination (pigeon peas, mungbeans, and soybeans). The experiment used a completely randomized design with one factor, namely the composition of each legume, consisting of 4 treatments and 5 repetitions. The treatment of the study consisted of P1 (pigeon peas), P2 (pigeon peas + mungbeans 1:1), P3 (pigeon peas + soybeans 1:1), and P4 (pigeon peas + mungbeans + soybeans 1:1:1). The results showed that composition of legume type had a significant effect on proximate levels, dissolved protein, protein digestibility, lactic acid, and pH, but not the total lactic acid bacteria LAB of yogurt. The protein content, digestibility, and the soluble protein of legume-yogurt increased by approximately 1.21-1.86%, 0.36-0.44%, and 0.81-1.30%, respectively. In conclusion, yogurt from a single type of legume produced lower proximate levels, dissolved protein, protein digestibility, lactic acid, and low pH, while the combination of two or three types showed higher values for these parameters. Among the combinations, pigeon peas yogurt + soy produced higher proximate, dissolved protein, protein digestibility, lactic acid, as well as lower pH compared to pigeon peas yogurt + mungbeans.